Model to support the learning process and generation of knowledge using collaborative tools. - Avila, S.R. (2021)
The current conditions of the pandemic, as a result of Covid-19, have led university teachers to look for ways to improve the learning process and the generation of knowledge, taking advantage of the use of information technologies. This research paper proposes a model to support the learning process and knowledge generation using collaborative tools considering two aspects of importance: the management of the learning activity and the implementation using specifically the collaborative wall Padlet to facilitate student participation, team collaboration and the corresponding feedback, reinforcing the generation of knowledge. The results obtained are quite encouraging, identifying based on a satisfaction survey that students build their knowledge based on collaborative learning.